ECONOMY IS THE BODY OF CIVIL SOCIETY LIFE - Utkirov Nusrat Kamilovich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: In this article, it is considered that the implementation of structural reforms, modernization and diversification of leading industries are of great importance in order to ensure the rapid development of the economy of the Republic of Uzbekistan today.